The mtDNA replication-related genes TFAM and POLG are associated with leprosy in Han Chinese from Southwest China. Issue 3 (December 2017) - Wang, Dong; Li, Guo-Dong; Fan, Yu; Zhang, Deng-Feng; Bi, Rui; Yu, Xiu-Feng; Long, Heng; Li, Yu-Ye; Yao, Yong-Gang
Highlights: TFAM and POLG affect risk to leprosy in Han Chinese. Rs1049432 and rs3176238 are cis eQTLs in human tissues. Differential mRNA expression of POLG in leprotic skin lesions. Abstract: Background: The pathogen Mycobacterium leprae of leprosy is heavily dependent on the host energy metabolites and nutritional products for survival. Previously we and others have identified associations of several mitochondrion-related genes and mitochondrial DNA (mtDNA) copy number alterations with leprosy and/or its subtype. We hypothesized that genetic variants of mtDNA replication-related genes would affect leprosy. Objective: We aimed to identify genetic associations between the mtDNA replication-related genes TFAM, POLG and leprosy. Methods: Genetic association study was performed in 2898 individuals from two independent sample sets in Yunnan Province, China. We first screened 7 tag SNPs of TFAM and POLG in 527 leprosy cases and 583 controls (Sample I). Expression quantitative trait loci (eQTL) analysis and differential mRNA expression were analyzed to discern potential effect of risk variants. The entire exon region of TFAM and POLG were further analyzed in 798 leprosy cases and 990 controls (Sample II; 4327 East Asians from the ExAC dataset was included as a reference control) by using targeted gene sequencing for fine mapping potentially causal variants. Results: Two tag SNPs of TFAM (rs1049432, P = 0.007) and POLG (rs3176238, P = 0.006) were associated with multibacillary leprosy (MB) in Sample I and the significance survived correction for multiple comparisons. SNPs rs1937 of TFAM (which was linked with rs1049432) and rs61756401 of POLG were associated with leprosy, whereas no potentially causative coding variants were identified in Sample II. The eQTL analysis showed that rs1049432 was a significant cis eQTL for TFAM in nerve tissue ( P = 1.20 × 10 −12 ), and rs3176238 was a significant cis eQTL for POLG in nerve ( P = 3.90 × 10 −13 ) and skin tissues ( P = 2.50 × 10 −11 ). Consistently, mRNA level of POLG was differentially expressed in leprotic skin lesions. Conclusions: Genetic variants of TFAM and POLG were associated with leprosy in Han Chinese, presumably by affecting gene expression.